Association between the maternal serum levels of 19 eicosanoids and pre‐eclampsia. Issue 3 (11th March 2016) - Long, Anxiong; Ma, Shungao; Li, Qian; Lin, Na; Zhan, Xia; Lu, Shuaijun; Zhu, Yuli; Jiang, Liansheng; Tan, Longyi
Abstract: Objective: To investigate whether serum levels of 19 eicosanoids are associated with pre‐eclampsia. Methods: A case–control study was performed using data for pregnant women with pre‐eclampsia, normotensive pregnant women, and nonpregnant women, for all of whom serum samples had been collected at a hospital in Shanghai, China, between December 2012 and December 2013. Ultra‐performance liquid chromatography–tandem mass spectrometry was used to measure the serum levels of 19 eicosanoids. Results: Overall, 49 pregnant women with pre‐eclampsia, 26 normotensive pregnant women, and 14 nonpregnant women were included. Women with pre‐eclampsia had significantly higher serum levels of 11, 12‐epoxyeicosatrienoic acid (11, 12‐EET), the hydroxyeicosatetraenoic acids 5‐HETE, 8‐HETE, 12‐HETE, and 15‐HETE, and leukotriene B4 than did women with a normal pregnancy and nonpregnant women, both before and after the onset of pre‐eclampsia ( P < 0.01 for all comparisons). Women with severe pre‐eclampsia had significantly higher serum levels of 5‐HETE, 15‐HETE, and leukotriene B4 than did women with mild pre‐eclampsia, women with a normal pregnancy, and nonpregnant women ( P < 0.01 for all comparisons). Conclusion: The eicosanoids 11, 12‐EET, 5‐HETE, 8‐HETE, 12‐HETE, 15‐HETE, and leukotriene B4 might play important parts in the occurrence and development of pre‐eclampsia.